Mirror, mirror : - Bercovitch, Vi (Shoreline, 1993)
A book of poetry in large print PUBCOMMENT: Vi Bercovitch was born in 1898. She was 94 when she asked us to publish her poems.She was a remarkable, lively and very attractive, tiny lady with winning ways to charm anyone. She lived to see her poetry published and the accolades pour in. In 1994 she died at 96, but her poems continue to inspire, provoke thought, and entertain.